Buster Keaton: Interviews - Sweeney, Kevin (Jackson, MS University Press of Mississippi, 2007)
With his trademark porkpie hat, floppy shoes, and deadpan facial expression, Buster Keaton (1895-1966) is one of the most iconic stars of Hollywood's silent and early sound eras. His elaborate sets, careful camerawork, and risky pratfalls have been mimicked by film comedians for generations. His short films, including One Week and Cops, and his feature-length comedies, such as Sherlock Jr., Go West, and The General, routinely appear on critics' lists of the greatest films of all time.Buster Keaton: Interviews collects interviews from the beginning of his career in the 1920s to the year before his death. The pieces here provide a critical perspective on his acting and cinematic techniques. Although the collection begins in the 1920s, at the height of Keaton's career, they also give insight on his work in Hollywood and television throughout the 1950s and 1960s. Including pieces by Studs Terkel and Rex Reed, as well as a French interview that has never before appeared in English, the book is a valuable resource on one of cinema's early geniuses.Kevin W. Sweeney is associate professor of philosophy at the University of Tampa.
Keywords: Keaton, Buster -- 1895-1966; 20th Century (1901-2000); Actor; Film director; USA